Філософія життя у пошуках людської сутності - Іменинник, В. О. (ХНУРЕ, 2020)
"Philosophy of life" is called the direction of Western philosophical thought of the late XIX – early XX century. The philosophers of this area bring to the fore the concept and principle of life. Representatives of the philosophy of life have accused traditional philosophy of having created a cult of reason and science. Most likely, not the natural sciences, but the humanities – philosophy, psychology, history, including the history of the spirit, the sciences of language, culture – form a problematic center for the study of philosophy of life.
Keywords: філософія життя